Materialism And The Locus Of The Subject Of Experiences - Smythe, Thomas W. (European Scientific Journal, ESJ, 2016)
The paper treats alternative views about a materialist conception of the subject of experiences or the self or person. Some views are that the self is the brain, or the whole person, or that there is no self or subject of experiences. We lay out each view and their advantages and disadvantages.